Analysis and Implementation of Online-Based Rice Sales (e-commerce) at UD. Toko Beras Santy - Tomi Gunawan; Dram Renaldi (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
Improvements in human resources have made rapid developments in technology and information. In the business sector the use of technology greatly affects sales and marketing, but not all business sectors have used technology in their sales and marketing. One way to increase the area of ​​marketing is to use internet technology that can cover many areas. With the existence of internet technology everyone from many areas can be connected easily and quickly. The use of the internet in the business sector is not only limited to the expansion of the marketing area but can also be used as a medium of transaction that uses the internet network called e-commerce which is very helpful for customers in purchasing a product. With the help of the Technology Acceptance Model or TAM method, researchers can understand the factors that influence the acceptance of the use of computer technology through 5 factors, namely, Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention Of Use, and Actual System Usage. TAM aims to explain the user's acceptance of an information system as well as with this e-commerce web can help in the selection of rice products quickly and expand the area of ​​product marketing.